1998
DOI: 10.1088/0022-3727/31/2/004
|View full text |Cite
|
Sign up to set email alerts
|

The cylindrical DC magnetron discharge: I. Particle-in-cell simulation

Abstract: The radial structure of a low-pressure cylindrical post-cathode direct-current magnetron discharge is investigated using a one-dimensional, electrostatic particle-in-cell code, incorporating non-periodic boundary conditions and an external circuit. Electron and ion collisions with a background gas of argon are modelled using Monte Carlo techniques. The radial structure of the discharge is examined for a range of operating conditions. Profiles of the electric potential, electric field and space charge density a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 46 publications
3
35
1
Order By: Relevance
“…They compared the calculated profiles of the ionization rate with the measurements of the radial profile of the current [3] and the axial profile of the optical emission [4]. Van der Straaten et al [15,16] recently performed a one-dimensional particle-in-cell/Monte Carlo (PIC/MC) simulation [17,18] of a cylindrical post-cathode dc magnetron and examined the complicated discharge structure in detail. Van der Straaten et al found that the discharge exhibits a transition from the positive-space-charge (PSC) mode at higher pressure to the negative-space-charge (NSC) mode at lower pressure.…”
Section: Introductionmentioning
confidence: 99%
“…They compared the calculated profiles of the ionization rate with the measurements of the radial profile of the current [3] and the axial profile of the optical emission [4]. Van der Straaten et al [15,16] recently performed a one-dimensional particle-in-cell/Monte Carlo (PIC/MC) simulation [17,18] of a cylindrical post-cathode dc magnetron and examined the complicated discharge structure in detail. Van der Straaten et al found that the discharge exhibits a transition from the positive-space-charge (PSC) mode at higher pressure to the negative-space-charge (NSC) mode at lower pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In the preceding paper we reported one-dimensional particle-in-cell-Monte Carlo collision (PIC-MCC) simulations of a cylindrical DC magnetron discharge which indicated the existence of a negative space charge (NSC) mode of operation at low pressures [1]. Unlike the positive space charge (PSC) mode which is observed in unmagnetized glow discharges and in magnetized discharges at higher pressures, which features a thin positive space charge sheath at the cathode (the cathode fall), the NSC mode is characterized by a broad negative space charge sheath at the anode, across which most of the applied potential appears.…”
Section: Introductionmentioning
confidence: 99%
“…Ions are therefore expected to leave the discharge more readily than are electrons. As discussed in [1], the positive space charge sheath, which forms at the cathode in unmagnetized discharges as a result of the large disparity in electron and ion mobilities, is not expected to exist under such conditions. Instead, the results of one-dimensional (1D) PIC simulations predict that a negative space charge region forms at the anode.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the applications that were developed using these coatings were in the field of semiconductors, hard coatings, and in wide variety of other applications [3][4][5]. In comparison to planar magnetrons, where the target is planar in shape, cylindrical magnetrons are not very much used for deposition purposes.…”
mentioning
confidence: 99%